Efficiency Asymmetry in Bangladesh One-Day International Cricket: A Data Envelopment Analysis of Batting and Bowling Performance (2016–2024) - Hossain, Rezwan; Khatun, Halima; Rahman, Md. Zillur (International Journal of Arts, Sciences and Education, 2026)
Since 2016, Bangladesh One-Day International cricket has been experiencing profound change, but the performance reliability is unstable with the changing world standards. The research question will examine the efficiency asymmetry between the batting and bowling units in an attempt to establish key determinants of match success. The researchers have used ESPNcricinfo Statsguru data (2016-2024) to analyze 57 players who passed 10 match criteria through Data Envelopment Analysis and the random forest model. The composite efficiency indexes were built with normalized measures of average, strike rate, economy, and wicket-taking ability. Bowling efficiency scores were significantly higher than batting efficiency scores (mean = 0.812 vs 0.724, p < 0.001). In separate fields, Mustafizur Rahman (178 wickets, economy 5.20) and Mushfiqur Rahim (4,630 runs, average 43.27) were top performers. The efficiency of bowling showed a higher correlation with the probability of winning (r=0.71) compared to batting (r=0.42), with 34.2 per cent of variance in predictive model features. Bowling performance generates match results much more than batting does in developing cricket countries. Competitive growth with sustainability requires tactical inversion to death-overs batting expertise and all-rounder resources of high-efficiency diversification. The study offers an evidence-based model of talent identification in Emerging Cricket Boards.